Thyroid Nodules Located in the Lower Pole Have a Higher Risk of Malignancy than Located in the Isthmus: A Single-Center Experience - Gulhan Duman; Baris Sariakcali (International Journal of Endocrinology)
Purpose. The aim of our study is to investigate whether thyroid nodules (TNs) localization has value as a predictor of malignancy. Ultrasonography provides very valuable information in the evaluation of TNs, but it does not correlate perfectly with histopathologic findings. Therefore, studies that will include new diagnostic methods that can improve these unknowns can be welcomed gratefully. Methods. This study was carried out retrospectively in a tertiary care center from September 2016 to January 2020. The study included 862 adult patients who have one or more nodules. Ultrasonography of characteristics of nodules such as echogenicity, content, margins, calcifications, size, and localization was recorded. Fine-needle aspiration biopsy (FNAB) was performed on dominant and suspicious 1142 nodules. Results. The patients were composed of 692 (80.3%) females and 170 (19.7%) males. Compared to nodules located in the isthmus; the malignancy risk increased 8.39 (OR: 8.39 (2.34–30.12), p = 0.001) times in the lower pole, 4.27 (OR: 4.27 (1.16–15.72), p = 0.029), times in the middle pole, 8.09 (OR: 8.09 (2.11–30.94), p = 0.002) times in the upper pole, and 7.63 (OR: 7.63 (1.95–29.81), p = 0.003) times in the nodules covering the whole of the lobe. Although the most nodular location was in the middle pole, the risk of malignancy was less than that in the lower and upper poles. Conclusions. Unlike the other localization studies, we found a higher risk of malignancy in the lower and similarly upper thyroid poles. Besides well-defined malignancy indicators in the literature and guidelines, localization information is promising for this purpose in the future.